Estudo estrutural e alguns aspectos ultraestruturais de ciliados comensais de invertebrados marinhos do litoral do Estado do Rio de Janeiro - Silva Neto, Inácio Domingos da (1987)
Several groups of ciliophora were found to be associated with marine invertebrates of the phyla Cnidaria, Mollusca and Echinodermata collected from litoral area of the state of Rio de Janeiro, Brazil. The Cnidaria (Anemonia sargassensis, Phylactis flosculifera and Bunodosoma caissarum) lodged in the gastrovascular cavities the Trofont of Foettingeria actiniarum (Claparède, 1863); Apostomatida. The Paleal cavity of the bivalve Anomalocardia brasiliana, showed great quantities of one atypical ciliate Haplofriidae (?); Astomatida. The digestive cavity of the Neoteredo reynei lodged several Metanycthoterus rancureli Laval & Tuffrau, 1973; Heterotrichida. Numerous individual of Euplotes balteatus (Dujardin, 1841); Hipotrichida and Parametopus circulabens (Biggar & Wenrich, 1932) Groliére et al, 1980; Heterotrichida were found in the digestive cavity of one Echinoderma Lytechinus variegatus. The starfishes Echinaster brasiliensis, Coscinasterias tenuispina, Astropecten armatus brasiliensis and Linckia guildingii lodged the epibionte Licnophora sp. Claparède, 1867; Heterotrichida. In the Enoplopatiria stellifera we found the ciliate Trichodina sp. Ehrenberg, 1838; Peritrichida, for light microscopy we have employed the techniques of Chatton-Lwoff (1930) (silver impregnation), Bodian (silvcr proteinate stain), adopted by Tuffrau (1964 and 1967) and Klein (1958), The Feulgen nuclear stain was also used. The ultrastructure studies (SEM) were limited to the ciliates F. actiniarum, E. balteatus and P. circumlabens the last one was also observed by TEM.